2020
DOI: 10.3389/fchem.2020.612418
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Enhanced Transition Metal Dichalcogenides as Charge Transport Layers in Metallophthalocyanine-Based Solar Cells

Abstract: Transitional metal dichalcogenides (TMDs), such as molybdenum disulfide (MoS2) have found application in photovoltaic cells as a charge transporting layer due to their high carrier mobility, chemical stability, and flexibility. In this research, a photovoltaic device was fabricated consisting of copper phthalocyanine (CuPc) as the active layer, exfoliated and Au-doped MoS2, which are n-type and p-type as electron and hole transport layers, respectively. XRD studies showed prominent peaks at (002) and other wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The peak observed at the Raman shift between 1460 and 1490 cm À1 provides information about the isoindole ring stretching, while the peak at 1535 cm À1 is a result of the clustering of B 1g and A 1g together in one vibration. 28 A high peak of the photoluminescence (PL) spectrum is seen at 1.64 eV in Fig. 1f, indicating that the material has good crystallinity.…”
Section: Resultsmentioning
confidence: 95%
“…The peak observed at the Raman shift between 1460 and 1490 cm À1 provides information about the isoindole ring stretching, while the peak at 1535 cm À1 is a result of the clustering of B 1g and A 1g together in one vibration. 28 A high peak of the photoluminescence (PL) spectrum is seen at 1.64 eV in Fig. 1f, indicating that the material has good crystallinity.…”
Section: Resultsmentioning
confidence: 95%
“…X-ray spectra (XRD) of the nanopowder prepared from MoS 2 showed that there are no clear peaks, and this indicates and confirms the nanostructure of MoS 2 is amorphous, and this is consistent with the data of the card (JCPDS No. 06-0097) [12][13][14], as in Fig. 3(a).…”
Section: X-ray Diffraction Spectrummentioning
confidence: 99%